Underwater and surface tethered swimming, lower limb strength, and somatic traits as the basic indices of young swimmers’ sprint performance - Sokołowski, Kamil; Bartolomeu, Raul F.; Krężałek, Piotr; Bragada, José A.; Pałka, Tomasz; Ambroży, Dorota; Strzała, Marek (Acta of bioengineering and biomechanics, 2023)
Purpose The ability to swim fast underwater is believed to be connected to lower limb strength and some somatic traits. The main purpose of the study was to evaluate strength and speed parameters based on the relationship between the strength of underwater dolphin kicks and the counter movement jump test (CMJ) among adolescent swimmers. Methods 48 adolescent male swimmers (13.47 ± 0.84 years) were examined for muscle mass of arms (mm arms), trunk (mm trunk), and legs (mm legs), body height (BH), and biological age (BA). An underwater tethered dolphin kicking test was conducted in a pool; average force (5Fave) and impulse per single cycle (5Iave) in the 5-s period were measured. Force indices (20Fave – average force from 20 seconds and 20Iave – average impulse per single cycle from 20 seconds) were also measured in 20-s tethered front crawl swimming. During CMJ testing, general lower body muscle motor capabilities were evaluated by extracting the work (CMJw [J]) and height (CMJh [m]) of the jump. Results The strongest correlations were observed between: (a) 5Fave and BH, mm arms and CMJw; (b) CMJw, mm arms, and 20Fave; (c) indices of swimming speed and 5Iave (BA control); (d) total swimming velocity and average tethered swimming force (BA control). Moderate partial correlations (BA control) were noted between speed indices of swimming race and CMJ. Conclusions The underwater tethered dolphin kick test is a useful predictor test of 50-m front crawl performance in young male swimmers, with better specificity for swimmers than CMJ results themselves.